Absolutely Truly - Frederick, Heather Vogel (Frederick, Heather Vogel. Pumpkin Falls mystery., 2014)
"Twelve-year-old Truly Lovejoy's family moves to a small town to take over a bookstore. Soon, she has to solve two mysteries involving a missing book and an undelivered letter"--